Programmable continuous chiral mineral gradient distribution material and application thereof
Through programmable continuous chiral mineral gradient distribution materials, the problem of adaptation of chiral multi-level structure microenvironment in osteocartilage interface repair is solved, better matching with natural tissues, and improved the repair effect of osteocartilage interface and biological Compatibility.
Patent Information
- Application Number
- CN202411327351.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2024-12-27
AI Technical Summary
The prior art is difficult to effectively repair bone-cartilage interface damage, especially due to the lack of gradient distribution and adaptation of chiral multilevel structure microenvironment, which leads to mismatch between the tissue engineering scaffold and the internal environment of natural bone, cartilage or tendon bone, affecting the repair effect.
Develop a programmable continuous chiral mineral gradient distribution material, through the composite slurry programming injection molding technology of powder and bonded phase, to form a gradient scaffold with porous and chiral multi-stage structure, to simulate the natural osteocartilage interface Microenvironment, regulates cellular behavior to promote repair.
It achieves better adaptation with natural tissue structure, improves the repair performance and biocompatibility of the osteocartilage interface, promotes the damage repair of bone, cartilage or tendon bone endpoints, and enhances the cell differentiation and proliferation effects.
Smart Images

Figure HDA0005055773370000011 
Figure HDA0005055773370000021 
Figure HDA0005055773370000031
Abstract
Description
Technical Field
[0001] The invention belongs to the field of nanomaterials and biomaterials, and in particular relates to a programmable continuous chiral mineral gradient distribution material and a preparation method and application thereof. Background Art
[0002] Chirality is a basic property of nature. It is widely present in organisms and is closely related to life activities, such as various helical structures of DNA, proteins, cells and tissues. Multi-level structures are a common phenomenon in nature. Since materials have multi-level organizational structures, they give them unexpected properties. Among them, studies have shown that the interior of bone tissue is a chiral multi-level structure. Studies have also confirmed that collagen fibers in the body are also chiral multi-level structures. Living organisms themselves are chiral multi-level structures that have specific selectivity for chiral environments. For example, chiral drugs play different roles in living organisms, thalidomide is the most typical example, and some chiral pesticides also have different insecticidal effects. At present, the relationship between chiral substances and living organisms has also become a hot topic of research. Therefore, the bionic chiral multi-level structure microenvironment is an indispensable factor in material design.
[0003] There are many causes of bone injury, including stress bone injury (BSI), open fracture, fatigue injury (Zhang Chunqiu, Wu Dankai, Guo Yuxiang, et al. Fatigue injury and repair of bone [J]. Journal of Biomedical Engineering, 2003 (01): 180-186.), joint dislocation and soft tissue injury (Xiong Enfu, Lan Qun, Yang Lin, et al. Rehabilitation needs of common bone and joint injuries [J]. Chinese Journal of Clinical Rehabilitation, 2003 (26): 3633-3634.). Stress bone injury occurs when the bone bears excessive or improper load, which is more common in athletes and military training (Kiuru MJ, HK, Ahovuo JA. Bone stress injuries. Acta Radiologica. 2004; 45(3): 000-000.); open fractures are caused by external forces that cause bones to break and be exposed to the air (Chen Xiaobin, Sun Tiansheng, Liu Zhi, et al. Application of damage control orthopedic principles in the treatment of severe multiple trauma in orthopedics [J]. North China National Defense Medicine, 2008, (04): 25-27.). The treatment of bone injuries needs to follow the damage control orthopedic principles (DCO) to comprehensively consider the type of injury, patient condition and the best time for treatment and rehabilitation.
[0004] Severe bone injuries may require the application of tissues or materials with similar structures and functions for transplantation and repair to prevent complications such as bone infection, bone nonunion, bone necrosis and bone defects. For bone defects, surgical treatment is the most effective method. Commonly used surgical techniques include bone transplantation, Masquelet technique and Ilizarov technique. Due to the complex tissue structure and low proliferation rate of chondrocytes, traditional clinical treatments such as microfracture, autologous / allogeneic osteochondral transplantation and cell-based technology have not shown significant efficacy in the self-repair of articular osteochondral defects. With the development of tissue engineering and materials science, the use of biomaterials for rotator cuff injury repair has become a research hotspot. These materials include untreated human tissue transplant materials, extracellular matrix materials and artificial synthetic materials (Xin Pengfei, Sun Youqiang, Li Jie, et al. The latest research hotspots of biomaterials for repairing rotator cuff injuries [J]. Chinese Journal of Tissue Engineering Research, 2020, 24(28): 4459-4464.). The nanofiber structure prepared by electrospinning technology is similar to the extracellular matrix of natural tendon tissue, providing new possibilities for the repair of rotator cuff injuries (Takakura Ken, Yang Zhen, Liu Shuyun, et al. Application of electrospinning technology in the repair of rotator cuff injuries [J]. Chinese Journal of Tissue Engineering Research, 2022, 26(04): 637-642.). However, osteochondral tissue is a gradient structure, with a smooth transition from cartilage to subchondral bone, involving changes in chondrocyte morphology and phenotype, extracellular matrix composition, collagen type and direction, and cytokines. A single treatment method cannot adapt to all stages. Therefore, it is necessary to induce osteochondrogenesis, promote the formation of osteochondral interface, and repair osteochondral defects by changing the microenvironment of cell growth.
[0005] The tendon-bone interface is a key structure connecting tendons and bones. It consists of four gradually transitioning regions, namely the tendon region, the unmineralized fibrocartilage region, the mineralized fibrocartilage region, and the bone region. Its function is essential for maintaining joint stability and transmitting mechanical loads. The tendon-bone interface is connected to the bone through a fibrocartilage interface, which is divided into a non-calcified region and a calcified region (KLMoffat, Wan-Hsuan S.Sun et al. "Characterization of the structure-function relationship at the ligament-to-bone interface." Proceedings of the National Academy of Sciences of the United States of America (2008). 7947-7952.). The existence of this structure enables the tendon to effectively connect with the bone and withstand tensile and compressive forces, thereby playing a role in resisting stretching and bearing loads during movement (Lv Jingtong, Shi Youxing, Wang Yunjiao, et al. Research progress in the repair of the structured interface of the tendon-bone junction [J]. Chinese Journal of Reparative and Reconstructive Surgery, 2019, 33(09): 1064-1070.). However, when this interface is damaged, such as after surgical repair, it is often difficult to restore the original biomechanical properties because the damaged interface is prone to form scar tissue rather than regenerating a normal structure (Li Ziyun, Wu Xiulin, Gao Haihan, et al. Research progress in the healing mechanism and treatment methods of tendon-bone interface injuries [J]. Chinese Journal of Traumatology, 2022, 38(07): 646-652.).
[0006] By understanding its structure-function relationship and exploring effective healing strategies, we can provide an important scientific basis for the repair and reconstruction of the tendon-bone interface. Studies have shown that the development and regeneration of each region in the tendon-bone interface are regulated by growth factors, inorganic ions, mechanical stimulation and hypoxic environment. Therefore, by regulating the inorganic ion gradient and growth factor gradient, a gradient scaffold system that promotes regional regeneration of the tendon-bone interface is constructed. According to the different gradients of the scaffold system, the tendon-bone interface cells are promoted to differentiate into tendons, cartilages and osteoblasts, and the healing of the tendon-bone attachment point is promoted simultaneously, so as to achieve the repair and regeneration of the tendon-bone interface. However, in many studies, the problem of matching the tissue engineering scaffold with the real environment inside natural bone, cartilage or tendon bone has not been truly solved. In addition to the pore gradient distribution, ion concentration gradient distribution, and cell gradient distribution, there is still a crucial point missing, which is the gradient distribution and adaptation of the chiral multi-level structure microenvironment. In particular, the gradient scaffold material with both continuous mineral gradient distribution and chiral multi-level structure microenvironment is the key to solving the above difficulties. Summary of the invention
[0007] The present invention discovers that the fusion of porosity, mineral gradient distribution and chiral multi-level structural microenvironment will form a structural microenvironment that synergistically adapts to the natural structure of the tissue, and has functions such as biocompatibility and regulation of cell behavior. Based on this property, a programmable continuous chiral mineral gradient distribution material is invented to further regulate the damage and repair of bones, cartilage interfaces / or tendon-bone attachments, etc., based on this, the present invention is completed.
[0008] In the first aspect, the present invention provides a programmable continuous chiral mineral gradient distribution material, which is obtained by programmed injection molding of a composite slurry formed by a powder and a binding phase; wherein the powder is a chiral multi-level structure bioceramic powder, and the binding phase is a binding phase containing polysaccharides or polysaccharide derivatives. The programmed injection molding process is performed in sequence according to the concentration gradient of the bioceramic powder and the binding phase. The process is completed by a programmed multi-needle grouting device. The programmed continuous chiral mineral gradient distribution material has the characteristics of biocompatibility and bone cartilage interface repair performance.
[0009] Further, the chiral multi-level structure bioceramic powder is selected from one or more of barium-based bioceramic powder, magnesium-based bioceramic powder, calcium-based bioceramic powder, microcrystalline glass bioceramic powder, alumina bioceramic powder, fluoroapatite bioceramic powder, aluminosilicate bioceramic powder, oxide bioceramic powder, nitride bioceramic powder, carbide bioceramic powder, boride bioceramic powder and / or silicide bioceramic powder;
[0010] Furthermore, when the chiral multi-level structure bioceramic powder is a barium-based bioceramic powder, the structural formula of the programmable continuous chiral mineral gradient distribution material is BaX, where X is an acid radical ion.
[0011] Furthermore, when the chiral multi-level structure bioceramic powder is a magnesium-based bioceramic powder, the structural formula of the programmable continuous chiral mineral gradient distribution material is MgX, where X is an acid radical ion.
[0012] Furthermore, the acid ions are anions generated during acid ionization, selected from one or more of phosphate, silicate, borate, carbonate, strontium, titanate, niobate, molybdate, tungstate, manganate, ferrite and / or vanadate.
[0013] Furthermore, when the chiral multi-level structure bioceramic powder is a calcium-based bioceramic powder, the calcium-based bioceramic powder is selected from one or more of hydroxyapatite bioceramic powder, β-tricalcium phosphate bioceramic powder, calcium silicate bioceramic powder, calcium borate bioceramic powder, calcium carbonate bioceramic powder and / or calcium phosphate bioceramic powder.
[0014] Furthermore, when the chiral multi-level structure bioceramic powder is a microcrystalline glass bioceramic powder, the microcrystalline glass bioceramic powder is selected from one or more of CaO-Al2O3-SiO2 bioceramic powder, β-CaO·SiO2 bioceramic powder, SiO2-Al2O3-B2O3 bioceramic powder, SiO2-Al2O3-ZnO bioceramic powder, SiO2-Al2O3-BaO bioceramic powder, SiO2-Al2O3-Na2O bioceramic powder, SiO2-Al2O3-K2O bioceramic powder, SiO2-Al2O3-Fe2O3 bioceramic powder and / or SiO2-Al2O3-Sb2O3 bioceramic powder.
[0015] Furthermore, when the chiral multi-level structure bioceramic powder is alumina bioceramic powder, the alumina bioceramic powder is selected from one or more of alumina bioceramic powder, activated alumina bioceramic powder, neutral alumina bioceramic powder and acidic alumina bioceramic powder.
[0016] Furthermore, when the chiral multi-level structure bioceramic powder is fluoroapatite bioceramic powder, Ca5F(PO4)3 bioceramic powder is preferred.
[0017] Furthermore, when the chiral multi-level structure bioceramic powder is an aluminosilicate bioceramic powder, the aluminosilicate bioceramic powder is selected from one or more of olivine-island silicate bioceramic powder, epidote (doubletetrahedra) island silicate bioceramic powder, tourmaline (rings oftetrahedra) cyclic silicate bioceramic powder, pyroxene (single chain) chain silicate bioceramic powder, amphibole (double chain) chain silicate bioceramic powder, mica-like silicate bioceramic powder and / or sheet silicate bioceramic powder.
[0018] Furthermore, when the chiral multi-level structure bioceramic powder is an oxide bioceramic powder, the oxide bioceramic powder is selected from one or more of Al2O3 bioceramic powder, ZrO2 bioceramic powder, magnesium oxide bioceramic powder, barium oxide bioceramic powder, silicon oxide bioceramic powder and / or titanium oxide bioceramic powder.
[0019] Furthermore, when the chiral multi-level structure bioceramic powder is a nitride bioceramic powder, the nitride bioceramic powder is selected from one or more of silicon nitride bioceramic powder, boron nitride bioceramic powder, aluminum nitride bioceramic powder, gallium nitride bioceramic powder and / or titanium nitride bioceramic powder.
[0020] Furthermore, when the chiral multi-level structure bioceramic powder is a carbide bioceramic powder, the carbide bioceramic powder is selected from one or more of titanium carbide bioceramic powder, zirconium carbide bioceramic powder, tungsten carbide bioceramic powder and / or silicon carbide bioceramic powder.
[0021] Furthermore, when the chiral multi-level structure bioceramic powder is a boride bioceramic powder, the boride bioceramic powder is selected from one or more of titanium boride bioceramic powder, tantalum boride bioceramic powder, vanadium boride bioceramic powder, chromium boride bioceramic powder, zirconium boride bioceramic powder, tungsten boride bioceramic powder, molybdenum boride bioceramic powder, niobium boride bioceramic powder and / or hafnium boride bioceramic powder.
[0022] Furthermore, when the chiral multi-level structure bioceramic powder is a silicide bioceramic powder, the silicide bioceramic powder is selected from one or more of manganese silicide bioceramic powder, iron silicide bioceramic powder, cobalt silicide bioceramic powder, nickel silicide bioceramic powder, titanium silicide bioceramic powder, zirconium silicide bioceramic powder, niobium silicide bioceramic powder, vanadium silicide bioceramic powder, niobium silicide bioceramic powder, tantalum silicide bioceramic powder, molybdenum silicide bioceramic powder, tungsten silicide bioceramic powder and / or barium silicide bioceramic powder.
[0023] Furthermore, the chiral multi-level structure bioceramic powder can be D-type, L-type and Rac-type (racemic) chiral multi-level structure bioceramic powder according to the selected chiral molecular configuration, as well as non-chiral bioceramic powder formed by not selecting chiral molecules.
[0024] Furthermore, the adhesive phase is a mixed liquid with a specific viscosity and a polysaccharide, a polysaccharide derivative, a protein and / or a protein derivative as a binder. The preparation steps of the adhesive phase are as follows:
[0025] S1: selecting a specific type of polysaccharide or polysaccharide derivative or protein or protein derivative or one or more combinations thereof as a binder;
[0026] S2 dissolves the binder in water or other solvents, and fully stirs to dissolve, so as to form a bonding phase with a specific viscosity.
[0027] Furthermore, the polysaccharide in step S1 is selected from one or more of chitosan, hyaluronic acid, sodium alginate, starch, cellulose, glycogen, gum arabic, polyfructose, agar, chondroitin sulfate, dermatan sulfate, laminar acid sulfate, heparin, heparan sulfate and / or mannan.
[0028] Furthermore, the polysaccharide derivatives in step S1 include polysaccharides derived from isomers, modified molecules and / or branched molecules of the above-mentioned polysaccharides.
[0029] Furthermore, the protein in step S1 is selected from one or more of collagen, fibrin, globulin, keratin, myoglobin and / or hemoglobin.
[0030] Furthermore, the protein derivatives in step S1 include derivative proteins such as isomers, modified molecules and / or branched molecules of the above-mentioned protein.
[0031] Furthermore, the mass percentage of the adhesive in the bonding phase of step S2 is 0.1% to 70% by weight, preferably 0.5% to 50% by weight.
[0032] Furthermore, the specific viscosity in step S2 can be adjusted according to the content of the adhesive, ranging from 0.1 to 30000 mPa·s (CPS), preferably from 1.1 to 10000 mPa·s (CPS).
[0033] Furthermore, the composite slurry is formed by adding the chiral multi-level structure bioceramic powder into the aforementioned bonding phase, and the steps of preparing the composite slurry include:
[0034] M4-1 Dispersing the chiral multi-level structure bioceramic powder in water or other solvents, where the solvent is the same as the solvent of the binder phase, to obtain a dispersion;
[0035] M4-2: Mix the above dispersion and the binder phase in a certain ratio, and then stir them evenly in a homogenizer to prepare a uniform composite slurry;
[0036] Furthermore, in the step M4-1, the solid content gradient range of the chiral multi-level structure bioceramic powder is 0% to 85% by weight, preferably 0% to 65% by weight.
[0037] Furthermore, the solid content gradient of the adhesive in step M4-1 ranges from 15% to 100% by weight, preferably from 35% to 90% by weight.
[0038] Furthermore, the viscosity of the composite slurry in step M4-2 is 5 to 8000 mPa·s (CPS), preferably 11 to 5000 mPa·s (CPS).
[0039] Furthermore, the programmed injection molding process is operated using a programmed multi-needle grouting device, and the specific steps are as follows:
[0040] M5-1 Add the composite slurry with different chiral multi-level structure bioceramic powder contents into the barrels according to the barrel number sequence from low concentration to high concentration;
[0041] M5-2 weaves the grouting program on the software;
[0042] M5-3 Select a suitable grouting mold;
[0043] M5-4 Select the appropriate mold temperature control program;
[0044] M5-5 runs the grouting program and performs grouting according to the set parameters. After temperature control and cooling, a frozen stent prototype is obtained;
[0045] M5-6 removes the solvent inside the scaffold by freeze drying to obtain a porous scaffold with a programmable continuous chiral mineral gradient distribution;
[0046] After drying, M5-7 was cross-linked with a certain concentration of cross-linking agent;
[0047] The product is washed with M5-8 detergent to neutrality and freeze-dried to obtain a well-crosslinked porous scaffold with a programmable continuous chiral mineral gradient distribution, which is the final product.
[0048] Furthermore, the content of the chiral multi-level structure bioceramic powder in the barrel of step M5-1 is 0% to 85% Wt, preferably 0% Wt, 5% Wt, 20% Wt, 40% Wt and / or 65% Wt.
[0049] Furthermore, the grouting procedure of step M5-2 includes but is not limited to the injected slurry volume, grouting sequence and grouting speed, etc.
[0050] Furthermore, in step M5-3, the grouting mold includes a cylindrical, cubic, spherical, conical and / or any shape complementary to the defect area.
[0051] Furthermore, the temperature control program in step M5-4 includes but is not limited to slow gradient cooling, rapid cooling and segmented cooling.
[0052] Furthermore, the temperature control program in step M5-4 is implemented by a temperature control module, preferably a temperature control tank.
[0053] In a second aspect, the present invention provides a method for preparing the programmable continuous chiral mineral gradient distribution material as described in the first aspect, the preparation method comprising the following steps:
[0054] M1 preparation of chiral multi-level structure bioceramic powder;
[0055] M2 uses polysaccharides, polysaccharide derivatives, proteins and / or protein derivatives as binders;
[0056] M3 prepares a bonding phase containing the bonding agent described in M2;
[0057] M4: mixing the chiral multi-level structure bioceramic powder with a binder to prepare a composite slurry containing chiral multi-level structure bioceramics with different concentration gradients and uniformly dispersed therein;
[0058] M5 uses a programmed multi-needle grouting device to programmably inject composite slurries with different concentration gradients to achieve gradient distribution of the mobile phase. The temperature is raised and lowered in the injection molding chamber through programming, and then freeze-dried to obtain the programmable continuous chiral mineral gradient distribution material.
[0059] Furthermore, the method for preparing the chiral multi-level structure bioceramic powder in step M1 is to add an asymmetry breaking inducer into the bioceramic.
[0060] Furthermore, the preparation method of the bioceramic is selected from one or more of a hydrothermal reaction method, a high temperature calcination method and / or a solvent thermal reaction method.
[0061] Furthermore, the asymmetry breaking inducer is a chiral molecule; wherein the chiral molecule is selected from one or more of chiral organic acids, chiral amino acids, chiral sugars, chiral esters and / or other chiral molecules.
[0062] Furthermore, when the chiral molecule is a chiral organic acid, the chiral organic acid is selected from one or more of tartaric acid, malic acid, lactic acid, camphorsulfonic acid, phenylglycine, cyclohexylglycine, tranexamic acid, cis-3-aminocyclohexanecarboxylic acid and / or ascorbic acid.
[0063] Furthermore, when the chiral molecule is a chiral amino acid, the chiral amino acid is selected from one or more of histidine, arginine, lysine, isoleucine, phenylalanine, leucine, tryptophan, alanine, methionine, proline, cysteine, aspartic acid, valine, serine, glutamine, tyrosine, aspartic acid, glutamic acid, glutamine and / or threonine.
[0064] Furthermore, when the chiral molecule is a chiral sugar, the chiral sugar is selected from glucose, fructose, galactose, ribose, deoxyribose, furanose, pyranose, maltose, sucrose, lactose and / or galactose; chiral alcohol: such as one or more of mannitol, xylitol, sorbitol, paclitaxel, resveratrol, ginkgo biloba polyprenols, (R)-(+)-1-phenyl-1-propanol, (S)-(-)-1-phenyl-1-propanol, phenylpropanol, iditol, 2-amino-1-propanol and / or galactitol.
[0065] Furthermore, when the chiral molecule is a chiral ester, the chiral ester is selected from diethyl tartrate and / or methyl lactate; chiral salts: such as one or more of histidinol dihydrochloride, ammonium tartrate, sodium ascorbate, carnitine hydrochloride, cysteine ethyl ester hydrochloride, sodium tartrate and / or sodium potassium tartrate.
[0066] Furthermore, when the chiral molecule is another chiral molecule, the other chiral molecule is selected from one or more of microcrystalline cellulose, ammonium penicillin, glutathione, lincomycin, tetracycline, levodopamine, biphenyl and / or helicene molecules.
[0067] Furthermore, the amount of chiral molecules added in step M1 is related to the amount of cationic ions added; wherein the molar ratio of the cations to the chiral molecules added is 1:0.05-10, preferably 1:0.1-10, more preferably 1:0.1-5, and even more preferably 1:0.2-5.
[0068] Furthermore, the configurations of the chiral molecule in step M1 include D-type, L-type and Rac-type (racemic).
[0069] Furthermore, the polysaccharide in step M2 is selected from one or more of chitosan, hyaluronic acid, sodium alginate, starch, cellulose, glycogen, gum arabic, polyfructose, agar, chondroitin sulfate, dermatan sulfate, laminar acid, heparin, heparan sulfate and / or mannan.
[0070] Furthermore, the polysaccharide derivatives in step M2 include polysaccharides derived from isomers, modified molecules and / or branched molecules of the above-mentioned polysaccharides.
[0071] Furthermore, the protein in step M2 is selected from one or more of collagen, fibrin, globulin, keratin, myoglobin, and hemoglobin.
[0072] Furthermore, the protein derivatives in step M2 include derivative proteins such as isomers, modified molecules and / or branched molecules of the above-mentioned proteins.
[0073] Furthermore, in the step M3, the bonding phase is to dissolve the binder in water or other solvents, and fully stir and dissolve to form a bonding phase with a specific viscosity.
[0074] Furthermore, the mass percentage of the adhesive in the adhesive phase is 0.1% to 70% by weight, preferably 0.5% to 50% by weight.
[0075] Furthermore, the specific viscosity can be adjusted according to the content of the adhesive, and the range is 0.1 to 30000 mPa·s (CPS), preferably 1.1 to 10000 mPa·s (CPS).
[0076] Furthermore, in step M4, the composite slurry is formed by adding the chiral multi-level structure bioceramic powder into the aforementioned bonding phase, and the steps of preparing the composite slurry include:
[0077] M4-1 Dispersing the chiral multi-level structure bioceramic powder in water or other solvents, where the solvent is the same as the solvent of the binder phase, to obtain a dispersion;
[0078] M4-2: Mix the above dispersion and the binder phase in a certain proportion, and then stir them evenly on a homogenizer to prepare a uniform composite slurry.
[0079] Furthermore, in the step M4-1, the solid content gradient range of the chiral multi-level structure bioceramic powder is 0% to 85% by weight, preferably 0% to 65% by weight.
[0080] Furthermore, the solid content of the adhesive in step M4-1 is 15% to 100% by weight, preferably 35% to 90% by weight.
[0081] Furthermore, the viscosity of the composite slurry in step M4-2 is 5 to 8000 mPa·s (CPS), preferably 11 to 5000 mPa·s (CPS).
[0082] Furthermore, the programmed injection molding process is operated using a programmed multi-needle injection device to achieve a mobile phase gradient distribution, and the specific steps are as follows:
[0083] M5-1 Add the composite slurry with different chiral multi-level structure bioceramic powder contents into the barrels according to the barrel number sequence from low concentration to high concentration;
[0084] M5-2 weaves the grouting program on the software;
[0085] M5-3 Select a suitable grouting mold;
[0086] M5-4 Select the appropriate mold temperature control program;
[0087] M5-5 runs the grouting program and performs grouting according to the set parameters. After temperature control and cooling, a frozen stent prototype is obtained;
[0088] M5-6 removes the solvent inside the scaffold by freeze drying to obtain a porous scaffold with a programmable continuous chiral mineral gradient distribution;
[0089] After drying, M5-7 was cross-linked with a certain concentration of cross-linking agent;
[0090] The product is washed with M5-8 detergent to neutrality and freeze-dried to obtain a well-crosslinked porous scaffold with a programmable continuous chiral mineral gradient distribution, which is the final product.
[0091] Furthermore, the content of the chiral multi-level structure bioceramic powder in the barrel of step M5-1 is 0% to 85% Wt, preferably 0% Wt, 5% Wt, 20% Wt, 40% Wt and / or 65% Wt.
[0092] Furthermore, the grouting procedure of step M5-2 includes but is not limited to the injected slurry volume, grouting sequence and grouting speed, etc.
[0093] Furthermore, in step M5-3, the grouting mold includes a cylindrical, cubic, spherical, conical and / or any shape complementary to the defect area.
[0094] Furthermore, the temperature control program in step M5-4 includes but is not limited to slow gradient cooling, rapid cooling and segmented cooling.
[0095] Furthermore, the temperature control program in step M5-4 is implemented by a temperature control module, preferably a temperature control tank.
[0096] In a third aspect, the present invention provides an application of the programmable continuous chiral mineral gradient distribution material as described in the first aspect in the preparation of medical biomaterials for treating bone defects, wherein the application is an application in the preparation of a programmable continuous chiral mineral gradient distribution material that improves curing performance, promotes bone chelation, and promotes bone regeneration and bone repair and healing ability.
[0097] Furthermore, the medical biomaterials for treating bone defects include, but are not limited to, trauma-related, wear-related, spinal-related, joint-related, orthopedic-related, and other materials that help support bone integration and bone interface connection.
[0098] Furthermore, the joint implants include but are not limited to artificial hip joints, artificial knee joints, artificial shoulder joints, artificial elbow joints, etc., and the other implants include but are not limited to sports medicine products and bone repair materials.
[0099] Furthermore, the joint injury is tendon-bone interface injury.
[0100] Furthermore, the tendon-bone interface injury is a rotator cuff injury.
[0101] Furthermore, during the preparation process of the programmable continuous chiral mineral gradient distribution material, a chiral multi-level structure microenvironment from the atomic level to the micron level is formed by introducing chiral multi-level structure minerals.
[0102] Furthermore, the chiral multi-level structure mineral is distributed in a continuous phase in a gradient manner through a programmable continuous casting technology.
[0103] Furthermore, the programmable continuous chiral mineral gradient distribution material achieves the effect of adapting to the natural structural microenvironment of the tissue by integrating porosity, mineral gradient concentration distribution and chiral multi-level structural microenvironment.
[0104] Furthermore, the ability to promote bone regeneration and bone repair and healing includes but is not limited to promoting cell differentiation into tendon, cartilage and bone.
[0105] Furthermore, the programmable continuous chiral mineral gradient distribution material changes the microenvironment of cell growth, induces osteochondrogenesis, and promotes the formation of the osteochondrocyte interface, thereby repairing osteochondrocyte defects.
[0106] Furthermore, in the repair of osteochondral defects, the programmable continuous chiral mineral gradient distribution material can selectively regulate cell behavior, such as proliferation and differentiation, and further regulate the damage and repair of the osteochondral interface.
[0107] Furthermore, the bone defect refers to the loss of normal bone due to various reasons.
[0108] Furthermore, the bone defect includes, but is not limited to, one or more of a traumatic bone defect, a congenital bone defect and / or an infectious bone defect.
[0109] Furthermore, the bone defect includes but is not limited to tendon-bone interface defect, alveolar bone defect, skull defect, femoral head necrosis defect, tumor bone necrosis defect and spinal bone defect.
[0110] Furthermore, the tendon-bone interface defect includes damage to bone, cartilage and / or tendon-bone attachment.
[0111] Furthermore, the tendon-bone interface defect is selected from one or more of a tendon area defect, an unmineralized fibrocartilage area defect, a mineralized fibrocartilage area defect and / or a bone area defect.
[0112] Beneficial Effects
[0113] The present invention provides a programmable continuous chiral mineral gradient distribution material and a preparation method and application. The method has a simple process and low cost. The prepared mineral gradient distribution material has porosity and a multi-level chiral structure, and has bone cartilage interface repair performance and good biocompatibility. In the preparation process, the programmable continuous chiral mineral gradient distribution material introduces chiral multi-level structure minerals to form a microenvironment of chiral multi-level structure from atomic level to micron level; the gradient distribution in the continuous phase is realized by programmable continuous casting technology; the porosity, mineral gradient concentration distribution and chiral multi-level structure microenvironment are integrated to improve the adaptability to the natural tissue structure microenvironment; and the bone cartilage interface damage repair is further regulated by selectively regulating cell behavior, such as proliferation and differentiation. Based on the above points, the overall damage repair of bone, cartilage and / or tendon bone attachment points is achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0114] Figure 1 A flowchart of a programmable continuous chiral mineral gradient distribution bracket, a preparation method and an application according to an embodiment of the present invention.
[0115] Figure 2 Scanning electron microscope image of the D-chiral multi-level structure bioceramic of Example 1 of the present invention.
[0116] Figure 3 Circular dichroism spectrum of the chiral multi-level structure bioceramic (D-, L- and R-chirality structures) of Example 1 of the present invention.
[0117] Figure 4 A physical picture of the programmable continuous chiral mineral gradient distribution support of Example 2 of the present invention.
[0118] Figure 5 Micro-CT grayscale image of the programmable continuous chiral mineral gradient distribution scaffold CS (chitosan) without adding chiral minerals according to Example 2 of the present invention.
[0119] Figure 6 Micro-CT gray value distribution and fitting curve diagram of the programmable continuous chiral mineral gradient distribution scaffold CS (chitosan) without adding chiral minerals according to Example 2 of the present invention.
[0120] Figure 7 Micro-CT grayscale image of the programmable continuous chiral mineral gradient distribution support with added non-chiral minerals according to Example 2 of the present invention.
[0121] Figure 8 The micro-ct gray value distribution and fitting curve diagram of the programmable continuous chiral mineral gradient distribution support with added non-chiral minerals according to Example 2 of the present invention.
[0122] Fig. 9Micro-CT grayscale image of the programmable continuous chiral mineral gradient distribution support with added D-chiral mineral according to Example 2 of the present invention.
[0123] Fig.10 The micro-ct gray value distribution and fitting curve diagram of the programmable continuous chiral mineral gradient distribution support with added D-chiral mineral according to Example 2 of the present invention.
[0124] Fig.11 Micro-CT grayscale image of the programmable continuous chiral mineral gradient distribution support with added L-chiral mineral according to Example 2 of the present invention.
[0125] Fig.12 The micro-ct gray value distribution and fitting curve diagram of the programmable continuous chiral mineral gradient distribution support with added L-chiral mineral according to Example 2 of the present invention.
[0126] Fig.13 Micro-CT grayscale image of the programmable continuous chiral mineral gradient distribution support with added R-chiral mineral according to Example 2 of the present invention.
[0127] Fig.14 The micro-ct gray value distribution and fitting curve diagram of the programmable continuous chiral mineral gradient distribution support with added R-chiral mineral according to Example 2 of the present invention.
[0128] Fig.15 A water drop contact angle diagram of the programmable continuous chiral mineral gradient distribution support of Example 2 of the present invention.
[0129] Fig.16 Figure 2 shows a cell culture diagram of a programmable continuous chiral mineral gradient distribution scaffold prepared in Example 2 of the present invention.
[0130] Fig.17 The osteochondrocyte repair modeling process of the programmable continuous chiral mineral gradient distribution scaffold with added L-chiral mineral prepared in Example 2 of the present invention and the repair effect diagram after 12 and 24 weeks.
[0131] Fig.18 Magnetic resonance imaging of the osteochondrium repair of the programmable continuous chiral mineral gradient distribution scaffold prepared in Example 2 of the present invention after 24 weeks. DETAILED DESCRIPTION
[0132] The specific embodiments of the present invention are further described below. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in the embodiments described below can be combined with each other as long as they do not conflict with each other.
[0133] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are commercially available unless otherwise specified.
[0134] the term
[0135] Chirality: refers to the geometric property that a structure cannot be superimposed on its mirror image through translation and rotation because of its lack of Sn symmetry.
[0136] Hierarchical structure: a structure that is ubiquitous in nature, referring to a structure that is superimposed step by step in scale or dimension from the atomic level to the macroscopic level.
[0137] Chiral meso-structure: refers to a multi-level structure in which the assembly units of a multi-level structure material are arranged and assembled in a chiral manner during its formation.
[0138] Chiral minerals refer to minerals that have chiral elements or chiral centers in their crystal structure and exhibit chiral properties. Chiral minerals are of great significance in the fields of geology and mineralogy, and also have certain research value in the fields of the origin and evolution of life. The following are some common chiral minerals:
[0139] Quartz: Quartz is a common chiral mineral with chiral elements in its crystal structure, which exhibits optical rotation properties. Quartz is optically active and can rotate the polarization direction of light.
[0140] Calcite: Calcite is also a common chiral mineral. There are chiral elements in its crystal structure, which exhibits properties such as birefringence and optical rotation. Calcite is often used in polarization optical research and experiments.
[0141] Mica: Mica is a type of flaky mineral containing chiral elements, with a special crystal structure, showing properties such as birefringence and optical rotation. Mica has important applications in petrology and experimental mineralogy.
[0142] Zircon: Zircon is a mineral containing zircon. The chiral element in the crystal structure makes it show chiral properties. Zircon is often used in earth science research and radiometric dating.
[0143] Apatite: Apatite is a phosphate mineral that contains chiral elements in its crystal structure and exhibits certain chiral properties. Apatite has extensive research value in geology and biomineralogy. The study of chiral minerals not only contributes to the development of geology and mineralogy, but also provides important clues for understanding the evolutionary history of earth materials, the origin of life, and biological evolution. By studying the properties and distribution of chiral minerals, we can explore the relationship and evolution process between the earth and life.
[0144] Programmable continuity refers to the regulation and optimization of the continuous process of the reaction by controlling conditions and parameters during chemical synthesis or material preparation. Compared with traditional intermittent reactions, this method has a higher degree of automation, higher reaction efficiency and better product purity. Programmable continuity is an efficient, controllable, safe and environmentally friendly chemical synthesis method, which has been widely used and studied in the fields of drug synthesis, chemical production and materials science. With the continuous advancement of technology and the continuous improvement of methods, programmable continuity will play an increasingly important role in the chemical industry.
[0145] Graded distribution: "Gradient concentration distribution" usually refers to the gradient property of the concentration of a substance or physical quantity in space as it changes with position. This distribution can describe the distribution law and change trend of a substance or physical quantity in space.
[0146] Example
[0147] An embodiment of the present invention provides a programmable continuous chiral mineral gradient distribution bracket and a preparation method and application thereof, see Figure 1 , Figure 1 The present invention discloses a programmable continuous chiral mineral gradient distribution support and a preparation method and application flow chart.
[0148] Example 1 Preparation of Chiral Multi-Level Structure Mineral Powder
[0149] 1.1 Preparation method
[0150] AD type chiral multi-level hydroxyapatite powder
[0151] (1) Calcium nitrate tetrahydrate (Ca(NO3) 2· 4H2O) was dissolved in water and stirred thoroughly to form solution A;
[0152] (2) dissolving the inducer D-type tartaric acid (C4H6O6) in water and stirring thoroughly to dissolve to form solution B;
[0153] (3) dissolving ammonium dihydrogen phosphate ((NH4)H2PO4) and urea (CH4N2O) in water and stirring thoroughly to dissolve to form solution C;
[0155] (4) At room temperature, B was quickly added to A under stirring to form a mixed solution, and stirring was continued for 5 minutes;
[0156] (5) At room temperature, C was slowly added dropwise to the mixed solution of AB under vigorous stirring to form a mixed reaction solution, and stirring was continued for 60 minutes;
[0157] (6) Then the mixture was transferred to a reactor and reacted at 180° C. for 24 hours. After the reaction was completed, the mixture was naturally cooled, centrifuged, washed alternately with deionized water and ethanol for 3 times, and then dried at 80° C. to obtain D-type chiral multi-level hydroxyapatite powder.
[0158] BL type and racemic Rcemica (R type) chiral multi-level structure hydroxyapatite powder
[0159] In the preparation process of this embodiment, L-type and R-type tartaric acid are used to react in step (2) to obtain L-type and R-type chiral multi-level structure hydroxyapatite powders.
[0160] 1.2 Test results
[0161] Figure 2 1 is a scanning electron microscope image of the D-type chiral multi-level structure hydroxyapatite powder of Example 1 of the present invention. Figure 2 It can be seen that the D-type chiral multi-level hydroxyapatite powder of this embodiment has a flower-like microstructure that is staggered and neatly arranged, has a uniform morphology, and presents a multi-level chiral structure.
[0162] Figure 3 is the circular dichroism spectrum of the chiral multi-level structure hydroxyapatite powder of Example 1 of the present invention, Figure 3 In the embodiment, the L-type powder, the D-type powder and the R-type powder are chiral multi-level structure hydroxyapatite powders synthesized corresponding to the L-type chiral molecule, the D-type chiral molecule and the export chiral molecule in Example 1. Figure 3 It can be seen that the chiral multi-level hydroxyapatite powders of Example 1 all exhibit circular dichroism, indicating that both have formed chiral mesoscopic structures and have corresponding optical properties. The R-type powder has no circular dichroism signal and does not exhibit a chiral structure.
[0163] The selection of different substances to make chiral and achiral ceramic powders has no effect on the scaffold. The ceramic powder is mainly a filler used to provide a chiral microenvironment and activity.
[0164] Example 2 Preparation of porous scaffolds with programmable continuous chiral mineral gradient distribution using chitosan as a binder
[0165] 2.1 Preparation method
[0166] AD-type porous support for programmable continuous chiral mineral gradient distribution
[0167] (1) Select chitosan as a binder;
[0168] (2) Dissolve chitosan in 1% acetic acid aqueous solution with a solid content of 4 wt% and stir thoroughly to dissolve to form a 6000
[0169] mPa·s viscosity of the bonding phase;
[0170] (3) Dispersing the D-type chiral multi-level structure bioceramic powder in water to obtain solid contents of 0 wt%, 0.2 wt%,
[0171] 0.5wt%, 1.0wt% and 1.3wt% of type D dispersion, respectively numbered A2-1, B2-1, C2-1, D2-1, E2-1; (4) the above dispersions were mixed with the binder phase in a volume ratio of 1:1, and then stirred thoroughly on a homogenizer.
[0172] The uniform D-type composite slurry with a viscosity of 3000 mPa·s was prepared, and the corresponding numbers were A2-2, B2-2, C2-2, D2-2, and E2-2.
[0173] (5) adding the D-type composite slurry containing the D-type chiral multi-level structure bioceramic powder into the barrels according to the barrel numbering sequence from low concentration to high concentration, and the corresponding numbers are viscosities A2-3, B2-3, C2-3, D2-3, and E2-3;
[0174] (6) The grouting program was weaved on the software, and the grouting was from high concentration to low concentration, namely E2-4, D2-4, C2-4, B2-4, and A2-4; the injected slurry volume was 50uL and the grouting speed was 1uL / s;
[0175] (7) Select a cylindrical grouting mold with a diameter of 6 mm and a depth of 10 mm;
[0176] (8) Select the mold temperature control program of slow gradient cooling, keep the temperature at room temperature for 10 minutes, start grouting, and wait until the grouting is completed. Then cool it to 0℃ and keep it for 30 minutes at a cooling rate of 1℃ per minute; then cool it to -20℃ and keep it for 60 minutes at a cooling rate of 5℃ per minute.
[0177] (9) Run the grouting program and perform grouting according to the set parameters. After temperature control and cooling, a frozen D-shaped support is obtained.
[0178] Frame Protoplasm;
[0179] (10) The solvent inside the scaffold was removed by freeze drying to obtain a D-type programmable continuous chiral mineral gradient distribution porous
[0180] Bracket;
[0181] (11) After drying, cross-link with 5% sodium hydroxide ethanol solution for 10 min;
[0182] (12) The product was then neutralized and washed with a dilute hydrochloric acid solution and then washed with pure water until it was neutral. It was then freeze-dried to obtain a cross-linked D-type porous scaffold with a programmable continuous chiral mineral gradient distribution.
[0183] BL, R and Ach programmable continuous chiral mineral gradient distribution porous scaffolds
[0184] In the preparation process of this embodiment, D-type, L-type, and R-type chiral multi-level structure hydroxyapatite powders and achiral powders are used in step (3) respectively, and the synthesized dispersions are recorded as D-type, L-type, R-type, and Ach-type dispersions, and the corresponding composite slurries are D-type, L-type, R-type, and Ach-type slurries. Finally, the corresponding scaffolds are recorded as D-type, L-type, R-type, and Ach-type scaffolds.
[0185] C. Pure Viscosity Agent Bracket
[0186] (1) Select chitosan as a binder;
[0187] (2) Dissolve chitosan in 1% acetic acid aqueous solution with a solid content of 4 wt% and stir thoroughly to dissolve to form a 6000
[0188] mPa·s viscosity of the bonding phase;
[0189] (3) then stirring thoroughly in a homogenizer to prepare a uniform slurry with a viscosity of 3000 mPa·s;
[0190] (4) Adding slurry into the barrel;
[0191] (5) The grouting program is compiled on the software, and the volume of injected slurry is 50uL and the grouting speed is 1uL / s;
[0192] (6) Select a cylindrical grouting mold with a diameter of 6 mm and a depth of 10 mm;
[0193] (7) Select the mold temperature control program of slow gradient cooling, keep the temperature at room temperature for 10 minutes, start grouting, and wait until the grouting is completed. Then cool it to 0℃ and keep it for 30 minutes at a cooling rate of 1℃ per minute; then cool it to -20℃ and keep it for 60 minutes at a cooling rate of 5℃ per minute.
[0194] (8) running the grouting program, performing grouting according to the set parameters, and obtaining a frozen stent prototype after temperature control and cooling;
[0195] (9) removing the solvent inside the scaffold by freeze drying to obtain a pure viscosifier scaffold;
[0196] (10) After drying, cross-link with 5% sodium hydroxide ethanol solution for 10 min;
[0197] (11) The mixture is then neutralized and washed with a dilute hydrochloric acid solution and then washed with pure water until it becomes neutral. The mixture is then freeze-dried to obtain a cross-linked pure viscosity agent scaffold.
[0198] 2.2 Test results
[0199] Figure 4 This is a real picture of the porous support with programmable continuous chiral mineral gradient distribution prepared in Example 2 of the present invention.
[0200] Figure 5-14 The CT grayscale cross-section images and corresponding grayscale value fitting curves of pure adhesive stents and Ach, D, L and R stents are shown respectively. It can be seen from the figure that the grayscale value of pure CS stent is evenly distributed, and the fitting curve is a horizontal straight line; the grayscale value images of Ach, D, L and R stents show that the density gradually decreases from bottom to top, and the fitting curve also shows a straight line with a certain slope, indicating that the density gradually decreases from bottom to top.
[0201] Fig.15 This is a picture of the water drop contact angle of a porous scaffold with a programmable continuous chiral mineral gradient distribution. It can be seen from the figure that the contact angle of the adhesive CS scaffold is 84.295°, and the contact angles of the Ach type, D type, L type and R type scaffolds are 0°, showing superhydrophilic properties.
[0202] Example 3 Preparation of porous scaffolds with programmable continuous chiral mineral gradient distribution using sodium hyaluronate as a binder
[0203] Preparation method
[0204] AD-type porous support for programmable continuous chiral mineral gradient distribution
[0205] (1) Sodium hyaluronate is selected as a binder;
[0206] (2) dissolving sodium hyaluronate in an aqueous solution with a solid content of 2 wt%, stirring and dissolving the solution to form an adhesive phase with a viscosity of 5000 mPa·s;
[0207] (3) Dispersing the D-type chiral multi-level structure bioceramic powder in water to obtain solid contents of 0 wt%, 0.2 wt%,
[0208] 0.5wt%, 1.0wt% and 1.3wt% of D-type dispersions, numbered A3-1, B3-1, C3-1, D3-1 and E3-1, respectively; (4) mixing the above dispersions with the binder phase in a volume ratio of 1:1, and then stirring them thoroughly on a homogenizer.
[0209] The uniform D-type composite slurry with a viscosity of 2500 mPa·s was prepared, and the corresponding numbers were A3-2, B3-2, C3-2, D3-2, and E3-2.
[0210] (5) adding the D-type composite slurry containing the D-type chiral multi-level structure bioceramic powder into the barrels according to the barrel numbering sequence from low concentration to high concentration, and the corresponding numbers are viscosities A3-3, B3-3, C3-3, D3-3, and E3-3;
[0211] (6) The grouting program is weaved on the software, and the grouting is from high concentration to low concentration, namely E3-4, D3-4, C3-4, B3-4, and A3-4; the injected slurry volume is 50uL and the grouting speed is 1uL / s;
[0212] (7) Select a cylindrical grouting mold with a diameter of 6 mm and a depth of 10 mm;
[0213] (8) Select the mold temperature control program of slow gradient cooling, keep the temperature at room temperature for 10 minutes, start grouting, and wait until the grouting is completed. Then cool it to 0℃ and keep it for 30 minutes at a cooling rate of 1℃ per minute; then cool it to -20℃ and keep it for 60 minutes at a cooling rate of 5℃ per minute.
[0214] (9) Run the grouting program and perform grouting according to the set parameters. After temperature control and cooling, a frozen D-shaped support is obtained.
[0215] Frame Protoplasm;
[0216] (10) The solvent inside the scaffold was removed by freeze drying to obtain a porous scaffold with a programmable and continuous gradient distribution of D-type chiral minerals.
[0217] (11) After drying, cross-link with 2% divinyl sulfone solution for 30 min;
[0218] (12) The product was then washed with pure water until it became neutral and freeze-dried to obtain a cross-linked D-type porous scaffold with a programmable continuous chiral mineral gradient distribution.
[0219] BL, R and Ach programmable continuous chiral mineral gradient distribution porous scaffolds
[0220] In the preparation process of this embodiment, D-type, L-type and R-type chiral multi-level structure hydroxyapatite powders and achiral powders are used respectively in step (3), and the synthesized dispersions are recorded as D-type, L-type, R-type and Ach-type dispersions, and the corresponding composite slurries are D-type, L-type, R-type and Ach-type slurries. Finally, the corresponding scaffolds are recorded as D-type, L-type, R-type and Ach-type scaffolds.
[0221] C. Pure adhesive stent
[0222] The stent without hydroxyapatite powder is a pure adhesive stent.
[0223] Example 4 Preparation of porous scaffolds with programmable continuous chiral mineral gradient distribution using collagen as a binder
[0224] Preparation method
[0225] AD-type porous support for programmable continuous chiral mineral gradient distribution
[0226] (1) Selecting collagen as a binder;
[0227] (2) Dissolve collagen in hexafluoroisopropanol solution with a solid content of 30wt% and stir thoroughly to dissolve to form a 4000
[0228] mPa·s viscosity of the bonding phase;
[0229] (3) dispersing the D-type chiral multi-level structure bioceramic powder in hexafluoroisopropanol to obtain D-type dispersions with solid contents of 0 wt%, 0.2 wt%, 0.5 wt%, 1.0 wt%, and 1.3 wt%, respectively, and the corresponding numbers are A4-1, B4-1, C4-1, D4-1, and E4-1;
[0230] (4) The above dispersions were mixed with the binder phase in a volume ratio of 1:1, and then fully stirred on a homogenizer to prepare a uniform D-type composite slurry with a viscosity of 2000 mPa·s, corresponding to the numbers A4-2, B4-2, C4-2, D4-2, and E4-2.
[0231] (5) adding the D-type composite slurry containing the D-type chiral multi-level structure bioceramic powder into the barrels according to the barrel numbering sequence from low concentration to high concentration, and the corresponding numbers are viscosities A4-3, B4-3, C4-3, D4-3, and E4-3;
[0232] (6) The grouting program was weaved on the software, and the grouting went from high concentration to low concentration, namely E4-4, D4-4, C4-4, B4-4, and A4-4; the injected slurry volume was 50uL and the grouting speed was 1uL / s;
[0233] (7) Select a cylindrical grouting mold with a diameter of 6 mm and a depth of 10 mm;
[0234] (8) Select the mold temperature control program of slow gradient cooling, keep the temperature at room temperature for 10 minutes, start grouting, and wait until the grouting is completed. Then cool it to -4°C and keep it for 30 minutes at a cooling rate of 1°C per minute; then cool it to -80°C and keep it for 60 minutes at a cooling rate of 5°C per minute.
[0235] (9) Run the grouting program and perform grouting according to the set parameters. After temperature control and cooling, a frozen D-shaped support is obtained.
[0236] Frame Protoplasm;
[0237] (10) Finally, the solvent inside the scaffold was removed by freeze drying to obtain a D-type porous scaffold with a programmable and continuous chiral mineral gradient distribution.
[0238] (11) After drying, cross-link with 50% glutaraldehyde vapor for 12 hours;
[0239] (12) It was then washed with pure water until the residual glutaraldehyde was completely removed and then freeze-dried to obtain a cross-linked D-type porous scaffold with a programmable continuous chiral mineral gradient distribution.
[0240] BL, R and Ach programmable continuous chiral mineral gradient distribution porous scaffolds
[0241] In the preparation process of this embodiment, D-type, L-type and R-type chiral multi-level structure hydroxyapatite powders and achiral powders are used respectively in step (3), and the synthesized dispersions are recorded as D-type, L-type, R-type and Ach-type dispersions, and the corresponding composite slurries are D-type, L-type, R-type and Ach-type slurries, and finally the corresponding scaffolds are recorded as D-type, L-type, R-type and Ach-type scaffolds.
[0242] C. Pure adhesive stent
[0243] The stent without hydroxyapatite powder is a pure adhesive stent.
[0244] Example 5 Preparation of porous scaffolds with programmable continuous chiral mineral gradient distribution using gelatin as a binder
[0245] Preparation method
[0246] AD-type porous support for programmable continuous chiral mineral gradient distribution
[0247] (1) Selecting gelatin as a binder;
[0248] (2) Dissolve gelatin in 1% acetic acid aqueous solution with a solid content of 10 wt% and stir thoroughly to form a 8000
[0249] mPa·s viscosity of the bonding phase;
[0250] (3) Dispersing the D-type chiral multi-level structure bioceramic powder in water to obtain solid contents of 0 wt%, 0.2 wt%,
[0251] 0.5wt%, 1.0wt% and 1.3wt% of D-type dispersions, correspondingly numbered A5-1, B5-1, C5-1, D5-1 and E5-1; (4) the above dispersions were mixed with the binder phase in a volume ratio of 1:1, and then stirred thoroughly on a homogenizer.
[0252] The uniform D-type composite slurry with a viscosity of 4000 mPa·s was prepared, and the corresponding numbers were A5-2, B5-2, C5-2, D5-2, and E5-2.
[0253] (5) Adding the D-type composite slurry containing the D-type chiral multi-level structure bioceramic powder into the barrels in order of barrel numbering from low concentration to high concentration, the corresponding numbers are A5-3, B5-3, C5-3, D5-3, and E5-3 in viscosity;
[0254] (6) The grouting program was weaved on the software, and the grouting was from high concentration to low concentration, namely E5-4, D5-4, C5-4, B5-4, and A5-4; the injected slurry volume was 50uL and the grouting speed was 1uL / s;
[0255] (7) Select a cylindrical grouting mold with a diameter of 6 mm and a depth of 10 mm;
[0256] (8) Select the mold temperature control program of slow gradient cooling, keep the temperature at room temperature for 10 minutes, start grouting, and wait until the grouting is completed. Then cool it to 0℃ and keep it for 30 minutes at a cooling rate of 1℃ per minute; then cool it to -20℃ and keep it for 60 minutes at a cooling rate of 5℃ per minute.
[0257] (9) Run the grouting program and perform grouting according to the set parameters. After temperature control and cooling, a frozen D-shaped support is obtained.
[0258] Frame Protoplasm;
[0259] (10) The solvent inside the scaffold was removed by freeze drying to obtain a D-type programmable continuous chiral mineral gradient distribution porous
[0260] Bracket;
[0261] (11) After drying, cross-link with 50% glutaraldehyde vapor for 4 hours;
[0262] (12) It was then washed with pure water until the residual glutaraldehyde was completely removed and then freeze-dried to obtain a cross-linked D-type porous scaffold with a programmable continuous chiral mineral gradient distribution.
[0263] BL, R and Ach programmable continuous chiral mineral gradient distribution porous scaffolds
[0264] In the preparation process of this embodiment, D-type, L-type and R-type chiral multi-level structure hydroxyapatite powders and achiral powders are used respectively in step (3), and the synthesized dispersions are recorded as D-type, L-type, R-type and Ach-type dispersions, and the corresponding composite slurries are D-type, L-type, R-type and Ach-type slurries. Finally, the corresponding scaffolds are recorded as D-type, L-type, R-type and Ach-type scaffolds.
[0265] C. Pure adhesive stent
[0266] The stent without hydroxyapatite powder is a pure adhesive stent.
[0267] Example 6 Cell experiment on porous scaffold with programmable continuous chiral mineral gradient distribution
[0268] 6.1 Sample Selection
[0269] In this test example, the D-type, L-type, R-type and Ach-type scaffolds and the pure adhesive phase scaffold of Example 2 were used to conduct cell experiments, and the cells used were bone marrow-derived mesenchymal stem cells.
[0270] 6.2 Test steps
[0271] 1) Extracting bone marrow-derived mesenchymal stem cells from the femur of mice, culturing and incubating them;
[0272] 2) Then proceed with planting, first place the sterilized scaffold at the bottom of the cell culture plate;
[0273] 3) Planting the dispersed BMSC cells on a porous scaffold with a programmable continuous chiral mineral gradient distribution for cultivation;
[0274] 4) After culturing for a period of time, the scaffold was removed, washed with PBS, and fixed with 4% PFA;
[0275] 5) After fixation, wash several times with PBS and then stain;
[0276] 6) Observe and take photos under a microscope.
[0277] 6.3 Test results
[0278] Fig.16 This is a microscope photograph of the adhesion and proliferation of cells on the porous scaffold with programmable continuous chiral mineral gradient distribution of the present invention.
[0279] like Fig.16 As shown, compared with the scaffold of pure adhesive phase, the porous scaffold with programmable continuous chiral mineral gradient distribution in Example 2 of the present invention can selectively promote cell adhesion and proliferation, among which the L-type scaffold is conducive to cell adhesion and proliferation, while the effects of D-type, R-type and Ach-type scaffolds are not obvious.
[0280] Example 7 In vivo experiment of porous scaffold with programmable continuous chiral mineral gradient distribution
[0281] 7.1 Sample Selection
[0282] In this test example, the D-type, L-type, R-type and Ach-type scaffolds of Example 2 and the pure adhesive phase scaffold were used to carry out osteochondral defect repair experiments.
[0283] 7.2 Test steps
[0284] 1) Select New Zealand rabbits for femoral defect modeling;
[0285] 2) Filling the sterilized porous scaffold with programmed continuous chiral mineral gradient distribution into the defect;
[0286] 3) Suture, disinfect the wound, and carry out repair and cultivation; some training and testing are also required during the repair process;
[0287] 4) After a period of incubation, the samples were removed, washed with PBS, and fixed with 4% PFA;
[0288] 5) After fixation, wash several times with PBS, then perform micro-CT photography, nuclear magnetic resonance photography, and section staining analysis;
[0289] 6) Finally, observe and take pictures under a microscope.
[0290] 7.3 Test results
[0291] Fig.17 These are photos of the experimental process of repairing femoral head osteochondral damage using a porous scaffold with programmed continuous chiral mineral gradient distribution of the present invention and photos after the repair. Fig.18 This is a nuclear magnetic resonance image of the porous scaffold with programmed continuous chiral mineral gradient distribution of the present invention for repairing femoral head osteochondral damage.
[0292] like Fig.17 As shown in the figure, the L-shaped stent has a good effect on the repair of osteochondral defects.
[0293] like Fig.18 As shown, the L-type scaffold has a better repair effect than the D-type, R-type and Ach-type scaffolds, showing a chirality-based selectivity effect.
Claims
1. A programmable continuous chiral mineral gradient distribution material, wherein the programmable continuous chiral mineral gradient distribution material is obtained by programmable injection molding of a composite slurry formed by a powder and a binder phase, wherein: The powder is a chiral multi-level structure bioceramic powder, and the binding phase is a binding phase containing polysaccharides or polysaccharide derivatives. The programmed injection molding process is performed in sequence according to the concentration gradient of the bioceramic powder and the binding phase. The process is completed by a programmed multi-needle grouting equipment. The programmed continuous chiral mineral gradient distribution material has the characteristics of biocompatibility and bone cartilage interface repair performance.
2. The programmable continuous chiral mineral gradient distribution material as described in claim 1 includes D-type, L-type and Rac-type (racemic) chiral mineral gradient distribution materials, as well as non-chiral mineral gradient distribution materials formed by not selecting chiral molecules, depending on the selected chiral molecular configuration.
3. The chiral multi-level structure bioceramic powder as described in claim 1 is selected from one or more of barium-based bioceramic powder, magnesium-based bioceramic powder, calcium-based bioceramic powder, microcrystalline glass bioceramic powder, alumina bioceramic powder, fluoroapatite bioceramic powder, aluminosilicate bioceramic powder, oxide bioceramic powder, nitride bioceramic powder, carbide bioceramic powder, boride bioceramic powder and silicide bioceramic powder.
4. The adhesive phase according to claim 1 is a mixed liquid with a specific viscosity and a polysaccharide, a polysaccharide derivative, a protein and / or a protein derivative as a binder. The preparation steps of the adhesive phase are as follows: S1: selecting a specific type of polysaccharide or polysaccharide derivative or protein or protein derivative or one or more combinations thereof as a binder; S2 dissolves the binder in water or other solvents, fully stirs and dissolves, and forms a bonding phase with a specific viscosity.
5. The composite slurry as claimed in claim 1 is formed by adding the chiral multi-level structure bioceramic powder into the aforementioned bonding phase, and the steps of preparing the composite slurry include: M4-1 Dispersing the chiral multi-level structure bioceramic powder in water or other solvents, where the solvent is the same as the solvent of the binder phase, to obtain a dispersion; M4-2: Mix the above dispersion and the binder phase in a certain proportion, and then stir them evenly on a homogenizer to prepare a uniform composite slurry.
6. The adhesive as claimed in claim 4, wherein the solid content gradient range is 15% to 100% wt, preferably 35% to 90% wt; the viscosity of the composite slurry is 5 to 8000 mPa·s (CPS), preferably 11 to 5000 mPa·s (CPS).
7. The programmed injection molding process according to claim 1 is operated using a programmed multi-needle grouting device to achieve a mobile phase gradient distribution, and the specific steps are as follows: M5-1 Add the composite slurry with different chiral multi-level structure bioceramic powder contents into the barrels according to the barrel number sequence from low concentration to high concentration; M5-2 weaves grouting procedures on the software, such as injection slurry volume, grouting sequence, grouting speed, etc.; M5-3 Select a suitable grouting mold, such as cylindrical, square, etc.; M5-4 Select the appropriate mold temperature control program, such as slow gradient cooling, rapid cooling, segmented cooling, etc.; M5-5 runs the grouting program and performs grouting according to the set parameters. After temperature control and cooling, a frozen stent prototype is obtained; M5-6 removes the solvent inside the scaffold by freeze drying to obtain a porous scaffold with a programmable continuous chiral mineral gradient distribution; After drying, M5-7 was cross-linked with a certain concentration of cross-linking agent; The product is washed with M5-8 detergent to neutrality and freeze-dried to obtain a well-crosslinked porous scaffold with a programmable continuous chiral mineral gradient distribution, which is the final product.
8. The barrel as claimed in claim 7, wherein the solid content gradient range of the added chiral multi-level structure bioceramic powder is 0% to 85% Wt, preferably 0% Wt, 5% Wt, 20% Wt, 40% Wt and / or 65% Wt.
9. A method for preparing a programmable continuous chiral mineral gradient distribution material as claimed in claim 1, the method comprising the following steps: M1 preparation of chiral multi-level structure bioceramic powder; M2 uses polysaccharides, polysaccharide derivatives, proteins and / or protein derivatives as binders; M3 prepares a bonding phase containing the bonding agent described in M2; M4: mixing the chiral multi-level structure bioceramic powder with a binder to prepare a composite slurry containing chiral multi-level structure bioceramics with different concentration gradients and uniformly dispersed therein; M5 uses a programmed multi-needle grouting device to programmably inject composite slurries with different concentration gradients to achieve gradient distribution of mobile phase. The injection molding chamber can be programmed to increase or decrease the temperature, and then freeze-dried to obtain the programmable continuous chiral mineral gradient distribution material.
10. The use of the programmable continuous chiral mineral gradient distribution material as claimed in claim 1 in the preparation of medical biomaterials for treating bone defects, wherein the application is the use of the programmable continuous chiral mineral gradient distribution material in the preparation of materials for improving curing performance, promoting bone chelation, promoting bone regeneration and bone repair and healing ability.
